(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This study discusses the role of collectors as essential agents in urban waste management work. Considering that, for the most part, these workers are part of a community excluded from the job market, their activities as members of associations and cooperatives need to be regulated in order to offer them better conditions for work and social life. Thus, through a bibliographic survey, it was verified how the role of these professionals as partners of the State still needs to be debated. In view of this, it is also essential to consider principles to serve as guides for the work of organized waste pickers, such as the solidarity economy, circular economy, self-managed organization and solidarity entrepreneurship. From this perspective, as a partner of the State, considering the role of the collector, it will be possible for partnerships to be more facilitated, signed and maintained in order to benefit socio-environmental management as well as the integration of these collectors in the socioeconomic chain of recycling, and with this, proving to be a viable alternative to confronting inequalities.